Klasifikasi Sentimen Masyarakat di Twitter terhadap Puan Maharani dengan Metode Modified K-Nearest Neighbor - Putra, Wahyu Eka; Fikry, Muhammad; Yusra; Yanto, Febi; Cynthia, Eka Pandu (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to address the challenges in classifying sentiment on Twitter regarding Puan Maharani by implementing the Modified K-Nearest Neighbor (MK-NN) method, supplemented with feature weighting and feature selection techniques. This method is designed to improve accuracy by assigning higher weights to important features and reducing data dimensions to avoid overfitting. Data is collected using a crawling technique on Indonesian-language tweets, which are then manually labeled and processed through a preprocessing stage. The testing results using the modified K-Nearest Neighbor (MK-NN) method with confusion matrices show the model's performance at three different values of K (3, 5, and 7) and data ratios of 90:10, 80:20, and 70:30. With a 90:10 data ratio and K=3, the method achieved the highest accuracy of 89.0%. These results indicate that the combination of MK-NN and related techniques is highly effective in sentiment classification, offering an innovative solution to the limitations of conventional methods. These findings have potential applications in public opinion analysis, particularly for supporting data-driven strategic decision-making.